Irrigated Grain Sorghum Response to Long-Term Nitrogen, Phosphorus, and Potassium Fertilization - A. Schlegel; D. Bond (Kansas Agricultural Experiment Station Research Reports, 2021)
Long-term research shows that phosphorus (P) and nitrogen (N) fertilizer must be applied to optimize production of irrigated grain sorghum in western Kansas. In 2020, N applied alone increased yields 60 bu/a, whereas N and P applied together increased yields up to 83 bu/a. Averaged across the past 10 years, N and P fertilization increased sorghum yields up to 82 bu/a. The application of 160 lb/a N (with P) produced the maximum yield in 2020, which is slightly less than the 10-year average (2011–2020). The application of potassium (K) has had no effect on sorghum yield throughout the study period. The 10-year average grain N content reached a maximum of ~0.7 lb/bu while grain P content reached a maximum of 0.15 lb/bu (0.34 lb P2O5/bu) and grain K content reached a maximum of 0.19 lb/bu (0.23 lb K2O/bu). At the highest N, P, and K rate, apparent fertilizer recovery in the grain was 33% for N, 69% for P, and 40% for K. Nitrogen fertilization increased soil organic matter and decreased soil pH. Phosphorus fertilization tended to maintain or increase soil test P levels.
Keywords: nitrogen fertilization; phosphorus fertilization; irrigated grain sorghum; long-term fertility; nutrient removal